Mapping The Relationship Between Virtual Reality and Bullying Prevention: An Analysis Of Bibliographic Coupling - Maryaeni, Maryaeni; Nastiti, Vinna Rahmayanti Setyaning; Oktaviani, Chintya Tria Diana; Reikisyifa, Clarissa Sanindita; Kenanga, Larynt Sawfa; Kusuma, Wahyu Andhyka; Wahyuni, Evi Dwi (Society of Visual Informatics, 2025)
Bullying prevention has become a significant topic in contemporary society. The bibliographic analysis method employed is bibliographic coupling, which allows for identifying relationships among relevant scientific articles to understand the role of technology in combating bullying. The research methodology involves identifying previous publications on virtual reality and bullying prevention from Scopus. Bibliographic analysis quantifies relationships between publications based on shared references. The bibliographic data collected focuses on VR-related literature and bullying prevention from various academic sources. This article discusses the interconnections among the reviewed articles regarding the impact of these findings, such as the development of VR applications that can enhance social skills and empathy, which are crucial factors in preventing bullying. Research results indicate a significant correlation between virtual reality and bullying prevention. Relevant prior studies include topics such as using virtual reality to avoid bullying through bystanders and victims, as well as simulating bullying to enhance bystander empathy. These studies provide information on the role of virtual reality technology in effectively combating bullying. Research findings are presented as descriptive and visual analyses using VOS viewer software. Additionally, the article underscores the importance of interdisciplinary collaboration in integrating VR into effective bullying prevention strategies, making us all part of a larger community working towards a common goal. Hopefully, this article will provide a foundation for future research and the development of technology applications with the potential to combat bullying.